Non-structural carbohydrate concentrations of Fagus sylvatica and Pinus sylvestris fine roots are linked to ectomycorrhizal enzymatic activity during spring reactivation - Rosinger, Christoph; Sandén, Hans; Godbold, Douglas L (Mycorrhiza, 2020)
We evaluated whether changes in fine root non-structural carbohydrate reserves of Fagus sylvatica and Pinus sylvestris trees influence potential enzymatic activities of their ectomycorrhizal symbionts from winter towards spring reactivation, and whether these changes influence potential soil enzymatic activities. We analyzed sugar and starch concentrations in the fine roots of Fagus sylvatica and Pinus sylvestris and potential activities of ß-glucosidase, ß-xylosidase, and cellobiohydrolase (as proxies for carbon-degrading enzymes) as well as leucine aminopeptidase and chitinase (as proxies for nitrogen-degrading enzymes) of their dominant ectomycorrhizal symbionts as well as in the soil. Sugar concentrations in the fine roots were significantly positively correlated with enzymatic activities of the ectomycorrhizal symbionts. In Pinus sylvestris, both carbon- and nitrogen-degrading enzyme activities showed significant positive correlations with fine root sugar concentrations. In Fagus sylvatica, fine root sugar concentrations were explicitly positively correlated with the activity of nitrogen-degrading enzymes. The chitinase activity in the soil was found to be strongly positively correlated with the enzymatic activity of the ectomycorrhizal symbionts as well as with fine root sugar concentrations. Fine root carbohydrate concentrations of Fagus sylvatica and Pinus sylvestris trees and enzymatic activities of their associated ectomycorrhizal fungi are connected. The specific nutrient demand of the tree species during spring reactivation may affect ectomycorrhizal enzymatic activity via carbon mobilization in the fine roots of Fagus sylvatica and Pinus sylvestris. Moreover, our results suggest that trees indirectly contribute to the degradation of fungal necromass by stimulating ectomycorrhizal chitinase activity in the soil.
Keywords: mykorhiza; borovice lesní; Mycorrhizae; sacharidy; Plant Roots; Fagus; kořeny rostlin; Carbohydrates; buk (rod); Pinus sylvestris